The Notorious Mrs. Ebbsmith - Pinero, Arthur Wing, 1855-1934 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Notorious Mrs. Ebbsmith" by Arthur Wing Pinero is a play first produced in 1895. Agnes Ebbsmith is a radical critic of marriage and champion of free love, living unmarried in Venice with Lucas, a politician who abandoned his wife and career for her. They plan to lecture and campaign together against social conventions. But when Lucas's relatives arrive to "arrange" matters, Agnes discovers her partner may not share her revolutionary convictions. As pressure mounts from family and friends, Agnes must confront whether her ideals can withstand reality. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Notorious_Mrs._Ebbsmith
Release date is 2005-03-14
E-text prepared by Stephen Bishop
Keywords: Marriage -- Drama; Man-woman relationships -- Drama; English drama -- 19th century; Adultery -- Drama; Great Britain -- Social conditions -- 19th century -- Drama